Mental Health of Mothers with Malnourished Children in Nepal: A Prospective Observational Study - Sharma, Asmita; Sharma, Yograj; Thapa, Asha; Kar, Nilamadhab (Journal of Nepal Health Research Council, 2024)
Background: Maternal mental health may influence the nutritional status of their children. It was intended to assess the mental health status of the mothers of children admitted to a nutrition rehabilitation center. We specifically explored the relationship between maternal mental health and malnutrition of the child; to observe any change of maternal depressive/anxiety symptoms and weight gain in the child following admission. Methods: In a prospective observational study, malnutrition of children was assessed based on weight for height z scores using the WHO Anthro-Survey-Analyser. We evaluated anxiety using the Generalized Anxiety Disorder Scale (GAD-7) and depression by Patient Health Questionnaire (PHQ-9). Demographic and clinical variables were collected. Results: The degree of malnutrition of the children at admission and discharge was: mild (3.6% v 31.7%), moderate (37.7% v 26.3%), severe (58.7% v 8.4%), and no malnutrition (0.0% v 33.5%) (p<0.001). At admission, 12% of mothers had anxiety, depression, or both, which decreased to 3.0% at the time of discharge. There was no difference in malnutrition scores among children of mothers with or without anxiety/depression at admission or discharge, except that children of depressed mothers continued to have significantly greater levels of malnutrition at discharge compared with the mothers without depression. Maternal anxiety or depression was not associated with the severity of malnutrition. Conclusions: A proportion of mothers of children with malnutrition had clinical anxiety and depression; and maternal mental health concerns, especially depression may influence the nutrition of children. It is imperative to explore maternal mental health routinely for malnourished children. Keywords: Anxiety; children; depression; malnutrition; mothers.